Peeking Under the Rug: Unseen Gender Troubles in Sri Lanka’s Sexual and Reproductive Health Sector - Kumar, R. (Springer Nature Singapore, 2024)
Sexual and reproductive health (SRH) policies and programs are driven by agendas that are often far removed from health. These agendas, in turn, are shaped by sociopolitical forces and processes that operate at global, national, and/or local levels. Sri Lanka’s public health system is internationally acclaimed for delivering free and accessible maternity care. The country’s maternal health indicators, superior to those reported from most other South Asian settings, are cited as evidence of its reproductive health achievements. This chapter employs a critical feminist political economy of health lens to examine dominant narratives of reproductive healthcare in Sri Lanka. It draws attention to four “macro” processes, namely, medicalization, commercialization, co-optation, and marginalization, that critically shape SRH in Sri Lanka. A gender lens that links sociopolitical forces and processes with SRH policies and programs helps to throw light on often neglected social justice and equity concerns that must be addressed in efforts to advance SRH in Sri Lanka and elsewhere.
Keywords: Sexual and reproductive health; Medicalization; Commercialization; Nationalisms; Marginalization; Critical feminist methodologies; Sri Lanka